Thermal-tectonic history of the Baogutu porphyry Cu deposit, West Junggar as constrained from zircon U-Pb, biotite Ar/Ar and zircon/apatite (U-Th)/He dating - Li, G.; Cao, M.; Qin, K.; Evans, Noreen; McInnes, Brent; Liu, Y. (Pergamon-Elsevier Science Ltd, 2013)
Understanding postmineralization tectonic movements in porphyry deposits, is critical to interpreting the complete thermal-tectonic history. This study reports new zircon U–Pb ages, hydrothermal biotite 39Ar/40Ar age, and zircon and apatite (U–Th)/He ages from the Baogutu porphyry copper deposit, which, in conjunction with pre-existing geochronology and thermochronology and inverse modeling simulations, constrain the thermal-tectonic history of the deposit. Zircon LA-ICP-MS U–Pb concordia ages indicate a Late Carboniferous age of 320.1 ± 2.2 Ma for the diorite complex and 309.8 ± 2.2 Ma for the mineralized granodiorite porphyry. Hydrothermal biotite selected from a quartz–biotite–chalcopyrite vein yields a plateau age of 311.0 ± 1.8 Ma which agrees with the age of the granodiorite porphyry and a previously reported molybdenite Re–Os age, and suggests that hydrothermal fluid circulated about 310 m.y. ago. Diorite and granodiorite porphyry yield weighted mean zircon (U–Th)/He ages of 200.6 ± 5.7 Ma and 241.1 ± 8.1 Ma, respectively, with ages ranging from 221.0 Ma to 174.3 Ma and 225.9 to 261.6 Ma. Weighted mean diorite and granodiorite porphyry apatite (U–Th)/He ages of 87.4 ± 2.3 Ma and 120.0 ± 4.2 Ma were obtained with ages ranging from 68.9 Ma to 100.8 Ma, and from 91.0 Ma to 152.0 Ma, respectively. The wide range of zircon (U–Th)/He ages may be due to the combined effects of U and Th zonation and radiation damage, and radiation damage effect may also account for the wide range of apatite (U–Th)/He ages.The combined effects of depth and cooling due to meteoric water circulation contribute to an older (U–Th)/He age for the granodiorite porphyry, relative to the diorite. A five-episode cooling rate history for the diorite can be deduced by inverse model simulation: fast cooling—moderate fast cooling—relatively slow cooling—fast cooling again—very slow cooling. The thermal and tectonic history of the wall rock indicates that it suffered significant far-field effects from the Qiangtang–Eurasia and Lhasa–Qiangtang collision, however, no visible thermal effect from the India–Asia collision is observed.